Menuju Pendidikan Kewarganegaraan yang Berkualitas dan Berintegritas: Revitalisasi Etika Profesi Guru PKN untuk Mempersiapkan Generasi Muda yang Bermoral dan Bertanggung Jawab - Dipo Piswatama; Sri Yunita (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
Towards quality citizenship education and integrity: revitalizing the professional ethics of PKN teachers to prepare a moral and responsible young generation. This means that the author focuses the research of this article on the importance of citizenship education, overcoming the moral and ethical crisis and solutions for PKN teachers to overcome the moral and ethical crisis for students. The aim of this research is to improve the quality of citizenship education for PKN students and teachers as agents of educational change to reduce the moral and ethical crisis for students. The research method used is descriptive research. The focus of the research is on the importance of citizenship education for students and the moral and ethical crisis of PKN teachers becoming agents of educational change who will reduce the moral and ethical crisis. The solution to this problem is the existence of socialization regarding the importance of citizenship education and the dangers of a moral and ethical crisis for students, the continued existence of professional and qualified teachers in order to advance Indonesian education while at the same time making the lives of the Indonesian people more intelligent.